Civilization threats to vestibular stimulation reception and sensory integration system development and their potential impact on speech development disorders - Szczygieł, Aleksandra (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
Modern devices facilitating childcare, such as car seats, deckchairs, walkers, or multimedia devices – smartphones, tablets and television, in addition to performing the function for which they were created – ensuring the child’s safety and keep their attention occupied, can also be the cause of some additional, unwanted consequences. Those side effects mostly concern movement restrictions, visual field limitations, maintaining position unnatural for the developmental stage, or reducing the number of verbal and non-verbal interactions with the parent. This is associated with potential disorders of developmental trajectories – delayed achievement of basic milestones, and with dysfunctions in forming of the correct sensory integration, maturation of the child’s vestibular system and, as the further consequence – problems associated with the proper development of speech. The article attempts to analyze existing literature connected to the impact of vestibular system on proper language development and on the creation of a sensory integration. In addition, it concerns the problem of so-called container baby syndrome – a set of developmental threats associated with leaving a child for too long inside such baby accessories as car seats, deckchairs, walkers or with too early exposure to multimedia. The results of authors own research on knowledge among the students, about the dangers of abuse of positioning devices and multimedia in childcare were also presented.